Dry eye among patients at the eye clinic of a secondary referral hospital - Abdul Muna'aim, Maimunah; Tey, Yin Yee; Mohamad Zafarullah, Alya Az-Zahra; Md. Salleh, Rafidah; Omar, Nazri (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: Dry eye is a common but under-diagnosed problem in the general population. Lack of standardised diagnostic protocol causes prevalence of dry eye varied widely in different populations. Nevertheless, effective management rests largely on the accurate diagnosis and identification of the contributing risk factors. Methods: In a cross sectional study, socio-demographic, lifestyle and medical history data were collected from 157 respondents. A validated six-item questionnaire was used to determine the dry eye symptoms. Dry eye was determined by using Schirmer’s test. Fluorescein staining test and tear break up time (TBUT) test were performed to characterise the dry eye. Results: Using the Schirmer’s test, 33.8% of respondents had dry eyes. The likelihood of dry eye increased among Malay females in the seventh decade. The most frequently reported symptom was sensation of dryness of the eye. Although only 22.6% of dry eye cases were symptomatic, up to 47.2% of them may developed surface changes detectable by fluorescein dye test. Ethnicity (p=0.019) and diabetes mellitus (p=0.049) were significantly associated with dry eye. Conclusion: Dry eye could be subclinical but clinical tests in potential risk groups can lead to better detection of this condition and allow prescription of appropriate treatment for affected patients.